Some Approximation Theorems by De La Vallee-Pousin Mean: Saleh Abdullah Rasheed Al-Mezel - Team, Support (Thai Journal of Mathematics, 2011)
In this paper we apply the generalized de la Vall´ee-Pousin mean to prove some Korovkin type approximation theorems. We also show by an example that there is a sequence of linear operators for which the Korovkin theorem does not hold but our theorem holds. Finally, we apply regular matrices in proving these theorems.